Analysing the effects of land use characteristics on passenger ridership of rail-based transit oriented development lessons from Pandan Indah and Ampang LRT Station - Bakri, Fatahsha Amira; Kadar Hamsa, Abdul Azeez (Eastern Asia Society for Transportation Studies (EASTS), 2017)
Malaysia has been undergoing rapid industrialization and economic growth since the 1970s. Klang Valley and its conurbation is overwhelmed by traffic jams, where people tend to travel by their own cars. Consequently, government concedes public transportation, especially in Light Rail Transit (LRT) as the decisive approach to relieving traffic congestion in Klang Valley. However, after several years of this public transport being operated, LRT has not been able to persuade people to shift travel from the use of private to public transport. The result of a research study found that the public acceptance of the public transport service is very disappointing compared to the LRT ability to receive and carry passengers in large numbers (Malaysia Economic Monitor, 2015). It is believed to be due to lack of cooperation between land use planning and rail-based public transportation (Kuala Lumpur Structure Plan 2020). The purpose of this paper is to examine the effects of land use characteristics on passenger ridership of rail-based Transit Oriented Development (TOD) at Pandan Indah and Ampang LRT station.The observational survey method was conducted to collect data on land use density and diversity of mixed land use within 1000m radius around the selected LRT station. Whereas, the passenger volume count method was used to count the passenger ridership on weekday covering both during peak hour and off-peak hour for twelve hours duration at the two selected stations.The method of analysis such as relationship based on calculated diversity and density were applied. The findings revealed that the presence of compact developments with a mix of uses surrounding transit station contribute to the increase of passenger ridership.